SERVICE WAITING TIME AND POSTPARTUM MOTHERS’ SATISFACTION IN PRIMARY HEALTHCARE: A CROSS-SECTIONAL STUDY - Andini Rida Meylida; Lia Kurniasari (Jurnal Kesehatan Kusuma Husada, 2026)
Background: The postpartum period is very important in efforts to reduce maternal mortality because most postpartum complications occur during this period. One way to improve the quality of health services at facilities is to reduce wait times. Long wait times can affect patients’ perceptions of service quality and reduce patient satisfaction. This study aims to analyze the correlation between service waiting time and maternal satisfaction during postpartum visits at the Pasundan Health Center in Samarinda City.Methods: The research used a quantitative, cross-sectional approach. The research sample consisted of 191 postpartum mothers selected through convenience sampling. Data were collected using patient satisfaction questionnaires and observation sheets recording patient arrival and discharge times, and analyzed using the Fisher Exact test with a significance level of 0.05.Results: The results showed that most of the mothers who received services in the waiting time ≤60 minutes were satisfied with the services provided (89.2%); on the other hand, in respondents with a waiting time of > 60 minutes, most of them stated that they were not satisfied with the service. The results of the Fisher Exact test showed a p-value of 0.001 (p<0.05), indicating a significant correlation between service waiting time and postpartum mothers’ satisfaction. Conclusion: Service waiting time has a significant correlation with maternal satisfaction at postpartum visits. Efforts to improve service efficiency, the queue system, and the quality of health workers’ communication are needed to enhance patient satisfaction and the quality of postpartum services in primary health facilities.